Recent progress in nanocomposites of carbon dioxide fixation derived reproducible biomedical polymers - Liu, Xin; Jiang, Zhiwen; Xing, Dejun; Yang, Yan; Li, Zhiying; Sun, Zhiqiang (Frontiers in Chemistry, 2022)
In recent years, the environmental problems accompanying the extensive application of biomedical polymer materials produced from fossil fuels have attracted more and more attentions. As many biomedical polymer products are disposable, their life cycle is relatively short. Most of the used or overdue biomedical polymer products need to be burned after destruction, which increases the emission of carbon dioxide (CO2). Developing biomedical products based on CO2 fixation derived polymers with reproducible sources, and gradually replacing their unsustainable fossil-based counterparts, will promote the recycling of CO2 in this field and do good to control the greenhouse effect. Unfortunately, most of the existing polymer materials from renewable raw materials have some property shortages, which make them unable to meet the gradually improved quality and property requirements of biomedical products. In order to overcome these shortages, much time and effort has been dedicated to applying nanotechnology in this field. The present paper reviews recent advances in nanocomposites of CO2 fixation derived reproducible polymers for biomedical applications, and several promising strategies for further research directions in this field are highlighted.